2013
DOI: 10.1103/physrevd.87.094034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the color glass condensate to dihadron correlations in proton-proton and proton-nucleus collisions

Abstract: We perform a detailed comparison of long range rapidity correlations in the Color Glass Condensate framework to high multiplicity di-hadron data in proton-proton and proton-lead collisions from the CMS, ALICE and ATLAS experiments at the LHC. The overall good agreement thus far of the non-trivial systematics of theory with data is strongly suggestive of gluon saturation and the presence of subtle quantum interference effects between rapidity separated gluons. In particular, the yield of pairs collimated in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
197
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(205 citation statements)
references
References 53 publications
8
197
0
Order By: Relevance
“…Our expression for two gluon inclusive production is directly relevant to recent calculations of ridge correlations in [89,90]. Ref.…”
Section: Jhep04(2014)075mentioning
confidence: 99%
See 2 more Smart Citations
“…Our expression for two gluon inclusive production is directly relevant to recent calculations of ridge correlations in [89,90]. Ref.…”
Section: Jhep04(2014)075mentioning
confidence: 99%
“…This term is particularly interesting since it gives the leading contribution to correlated gluon emission as discussed in [88]. Approximate numerical implementation of this term has been used to describe the observed ridge correlations in p-p and p-A collisions at LHC in [89,90]. The contribution of this term to the cross section is…”
Section: Inclusive Two Gluon Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the disagreement could be that all initial state correlations that lead to an elliptic anisotropy 1 [17,18,19,20,21,22,23] are neglected. Additionally, the description of the proton in the IP-Glasma model is oversimplified.…”
Section: Ip-glasma + Musicmentioning
confidence: 99%
“…Thus an alternative interpretation could be that, instead of a ridge, the dynamically important phenomenon is actually a dip at a particular small, but nonzero, value of δφ. A number of authors have made comments and suggested explanations for the same-side ridge, including [3]- [19] .…”
Section: Introductionmentioning
confidence: 99%